2020
DOI: 10.1371/journal.pone.0221136
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of trap confinement on personality measurements in two terrestrial rodents

Abstract: In recent years, consistent individual differences in behavior, or personalities, have been a topic of increasing interest as researchers strive to understand and predict the responses of individuals and populations to anthropogenic changes. Behavioral studies in wild populations often require that animals are live trapped before behavioral observation can occur, and this is especially true in studies investigating animal personalities. However, it is unknown whether the amount of time confined to a live trap … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
(98 reference statements)
3
11
0
Order By: Relevance
“…Significant results (0 not included in the 95% CIs) personality traits for red squirrels, in both alpine and plain sites (Brehm & Mortelliti, 2018;Carter et al, 2013). This is similar to other studies on the same species, where repeatabilities for activity and immobility were also moderate (Mazzamuto et al, 2019;Santicchia, Wauters, Piscitelli, et al, 2020;Wauters et al, 2019), and on other studies on rodents where repeatability of activity measured in the OFT were from moderate to high (Tamiasciurus hudsonicus: Boon et al, 2008;Tamias striatus: Montiglio et al, 2012;Sciurus carolinensis: Mazzamuto et al, 2019, Santicchia, Wauters, Dantzer, et al, 2020Marmota flaviventer: Petelle et al, 2019;Peromyscus maniculatus, Myodes gapperi, Blarina brevicauda: Brehm et al, 2019, Brehm et al, 2020. Previous studies on the same species and on a different squirrel species also found low repeatability values for exploration measured in the OFT (Sciurus vulgaris: Santicchia, Wauters, Piscitelli, et al, 2020;Wauters et al, 2019;Sciurus carolinensis: Santicchia, Wauters, Dantzer, et al, 2020) and among-individual variation in the duration of exploration behaviours in the OFT was low, compared to other behavioural measures taken during the same tests (see Table S2; Santicchia, Wauters, Dantzer, et al, 2020; Table 1; Santicchia, Wauters, Piscitelli, et al, 2020; (Boon et al, 2008;Boyer et al, 2010;Martin & Réale, 2008;Patterson & Shulte-Hostedde, 2011).…”
Section: Repeatability Of Oft Personality Traitssupporting
confidence: 86%
“…Significant results (0 not included in the 95% CIs) personality traits for red squirrels, in both alpine and plain sites (Brehm & Mortelliti, 2018;Carter et al, 2013). This is similar to other studies on the same species, where repeatabilities for activity and immobility were also moderate (Mazzamuto et al, 2019;Santicchia, Wauters, Piscitelli, et al, 2020;Wauters et al, 2019), and on other studies on rodents where repeatability of activity measured in the OFT were from moderate to high (Tamiasciurus hudsonicus: Boon et al, 2008;Tamias striatus: Montiglio et al, 2012;Sciurus carolinensis: Mazzamuto et al, 2019, Santicchia, Wauters, Dantzer, et al, 2020Marmota flaviventer: Petelle et al, 2019;Peromyscus maniculatus, Myodes gapperi, Blarina brevicauda: Brehm et al, 2019, Brehm et al, 2020. Previous studies on the same species and on a different squirrel species also found low repeatability values for exploration measured in the OFT (Sciurus vulgaris: Santicchia, Wauters, Piscitelli, et al, 2020;Wauters et al, 2019;Sciurus carolinensis: Santicchia, Wauters, Dantzer, et al, 2020) and among-individual variation in the duration of exploration behaviours in the OFT was low, compared to other behavioural measures taken during the same tests (see Table S2; Santicchia, Wauters, Dantzer, et al, 2020; Table 1; Santicchia, Wauters, Piscitelli, et al, 2020; (Boon et al, 2008;Boyer et al, 2010;Martin & Réale, 2008;Patterson & Shulte-Hostedde, 2011).…”
Section: Repeatability Of Oft Personality Traitssupporting
confidence: 86%
“…The test is conducted prior to marking animals and once per session (to avoid test habituation) on new and recaptured individuals (minimum interval between tests is one month). In our previous work [26,36] we showed that trap confinement does not affect our behavioural measurements and that personality does not affect trappability, thus demonstrating that our sample is not biased towards certain personality types.…”
Section: (C) Behavioural Measurementssupporting
confidence: 53%
“…The area covered by each trapping grid (0.81 ha) was, at a minimum, less than 10% the area covered by each treatment and large enough to encompass multiple home-ranges of individual small mammals. Further details on methods are available in [9,26,35,36].…”
Section: (B) Small Mammal Trapping and Handlingmentioning
confidence: 99%
“…2018, Brehm et al. 2020) and microhabitat selection (Dueser and Shugart 1978, Longland and Price 1991, Mortelliti and Boitani 2007, Kellner and Swihart 2014).…”
Section: Introductionmentioning
confidence: 99%